Impact of the Major Baltic Inflow in 2014 on Manganese Cycling in the Gotland Deep (Baltic Sea) - Dellwig, Olaf; Schnetger, Bernhard; Meyer, David; Pollehne, Falk; Häusler, Katharina; Arz, Helge W. (Frontiers in Marine Science, 2018)
The deep basins of the Baltic Sea, including the Gotland and Landsort Deeps, are well known for the exceptional occurrence of sedimentary Mn carbonate. Although the details of the mechanisms of Mn carbonate formation are still under debate, a close relationship with episodic major Baltic inflows (MBIs) is generally assumed, at least for the Gotland Basin. However, the few studies on Mn cycling during MBIs suffer from a limited temporal resolution. Here we report on Mn dynamics in the water column and sediments of the Gotland Deep following an MBI that entered the Baltic Sea in December 2014. Water column profiles of dissolved Mn were obtained at a monthly to bi-monthly resolution between February 2015 and March 2017 and revealed an impact of the MBI on the Gotland Deep bottom waters beginning in March 2015. Water column profiles and budget estimates provided evidence for remarkable losses of dissolved Mn associated with the enhanced deposition of Mn oxide particles, as documented in sediment trap samples and surface sediments. In July 2015, subsequent to the nearly full oxygenation of the water column, clear signals of the re-establishment of bottom water anoxia appeared, interrupted by a second inflow pulse around February 2016. However, dissolved Mn concentrations of up to 40 µM in the bottom waters in June 2016 again indicated a pronounced reduction of Mn oxide and the escape of dissolved Mn back into the open water column. The absence of substantial amounts of Mn carbonate in the surface sediments at the end of the observation period suggested that the duration of bottom water oxygenation plays an important role in the formation of this mineral. Data from both an instrumental time series and a dated sediment core from the Gotland Deep supported this conclusion. Enhanced Mn carbonate formation occurred especially between the 1960s and mid-1970s, when several MBIs caused a long-lasting oxygenation of the water column. By contrast, Mn carbonate layers were much less pronounced or even missing after single MBIs in 1993, 2003, and 2014, each of which provided a comparatively short-term supply of O2 to the deeper water column.